Nextgen Enterprise: Stephaven Shoe Rack (Blueprint) / Nur Aina Nadia Abdul Latib ... [et al.]. - Abdul Latib, Nur Aina Nadia; Halim Ruzi, Nur Ainaa Syafiqah; Abdul Rahman, Nur Aisya Izzati; Jemaron, Nur Ayuni Nabila; Abdul Hadi, Nur Nuha (2025)
NextGen Enterprise is changing the face of home organisation with its state-of-the-art product, StepHaven Shoe Rack. StepHaven is known as an environmentally friendly and smart storing device for shoes which integrates automation, eco-friendly materials and sanitation. StepHaven is a modern alternative for the traditional shoe racks. StepHaven features a solar-powered conveyor belt, motion-sensitive LED lights, and an inbuilt sanitizer and diffuser which is composed of eco-friendly materials and odor suppression. StepHaven is a new alternative to traditional static storing. In addition, it is composed of biodegradable kenaf fiber. StepHaven is an environmentally friendly alternative that will be a solution to decrease the waste and lower carbon footprint. On the other hand, it is also purposely designed for modern living spaces as it portrays sleek and compact design. The StepHaven is definitely ideal for apartments, condominiums, offices, hotels, fitness centres, and retail stores. Besides, wherever maximization and organisation of spaces become a necessity. StepHaven redefines storing shoes in a new and efficient manner, enhancing routine work in a sanitary and efficient manner. Not to forget, it is integrated with technology, environment, and usability in harmony.